2014
DOI: 10.2459/jcm.0000000000000206
|View full text |Cite
|
Sign up to set email alerts
|

Relative efficacy and safety of direct oral anticoagulants in patients with atrial fibrillation by network meta-analysis

Abstract: BackgroundMuch direct evidence has proved that the novel oral anticoagulants (NOACs) are noninferior or superior to warfarin for stroke prevention in patients with nonvalvular atrial fibrillation, and lead to a relevant decrease in bleeding profiles. However, no study has compared NOACs with each other head-to-head. The current study is a network meta-analysis aiming to assess the efficacy and safety of NOACs.MethodsCochrane library, Pubmed NCBI, EMBASE and MEDLINE were systematically searched for randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 28 publications
3
34
0
2
Order By: Relevance
“…In other NMAs assessing the efficacy and safety of NOACs in the prevention of thromboembolic events in NVAF patients apixaban was found to be associated with fewer bleeding events compared with edoxaban, dabigatran and rivaroxaban [Fu et al 2014;Mantha and Ansell, 2012;Lip et al 2012]. In a previously published indirect comparison analysis of NOACs on secondary IS prevention in patients with NVAF, dabigatran 110 mg was associated with a lower risk for hemorrhagic stroke (HR 0.15;) and intracranial bleeding (HR 0.27; 95% CI 0.10-0.73) compared with rivaroxaban.…”
Section: Discussionmentioning
confidence: 99%
“…In other NMAs assessing the efficacy and safety of NOACs in the prevention of thromboembolic events in NVAF patients apixaban was found to be associated with fewer bleeding events compared with edoxaban, dabigatran and rivaroxaban [Fu et al 2014;Mantha and Ansell, 2012;Lip et al 2012]. In a previously published indirect comparison analysis of NOACs on secondary IS prevention in patients with NVAF, dabigatran 110 mg was associated with a lower risk for hemorrhagic stroke (HR 0.15;) and intracranial bleeding (HR 0.27; 95% CI 0.10-0.73) compared with rivaroxaban.…”
Section: Discussionmentioning
confidence: 99%
“…In pivotal RCTs, DOACs have demonstrated net clinical benefit compared with warfarin, mainly driven by a significant reduction of intracranial bleedings [6][7][8][9]. However, relevant differences in the incidence of major and gastrointestinal bleeding have been observed among DOACs, and apixaban seems to have the best safety profile, with a lower incidence of major bleeding [10][11][12] including gastrointestinal bleeding [13,14]. The economic value of apixaban has been demonstrated in an independent cost-effectiveness analysis conducted in UK and based on the data from a network meta-analysis of 23 RCTs [12], which showed that apixaban has a slightly higher expected quality-adjusted life expectancy (QALYs: 5.49 vs. 5.45 of rivaroxaban, 5.42 of dabigatran 150 mg, and 5.41 of edoxaban 60 mg) and the highest probability of being the most cost-effective first-line therapy for AF (close to 60% for willingness to pay thresholds of £ 20,000-30,000).…”
Section: Discussionmentioning
confidence: 99%
“…The results show that apixaban has a better safety profile in comparison to the other DOACs. Indeed it was associated with fewer bleeding events of any type (OR = 0.81; CI95%: 0.89-0.74) than edoxaban 60 mg QD and less major and GI bleeds than dabigatran 150 mg (major: OR = 0.75; CI95%: 0.61-0.90; GI: OR = 0.59; CI95%: 0.41-0.82) and rivaroxaban (major: OR = 0.67; CI95%: 0.82-0.55; GI: OR = 0.58; CI95%: 0.86-0.43) [11]. Finally, an indirect comparison analysis based on the phase III clinical trials found that there were no significant efficacy differences between edoxaban 60 mg QD and apixaban 5 mg BID, but apixaban was associated with lower clinically relevant non-major bleeding (HR = 0.79; CI95%: 0.70-0.90) and gastrointestinal bleeding (HR = 0.72; CI95%: 0.55-0.96) [14].…”
Section: Estimating the Cost-effectiveness Of Treatment For Preventiomentioning
confidence: 99%
See 2 more Smart Citations